English Talk Class Based Telegram (E-talk Castel): An Innovative and Creative Strategy to Stimulate Students' Speaking Skill - Ramlan Setiawan; Nining Candra Wahyuni (Universitas Muhammadiyah Semarang, 2017)
This paper showed the role of E-talk Castel?s model in improving students speaking skill in English. This model stimulates students to speak actively everyday by using recording tool in telegram application. There are many topics to be discussed in daily as well as weekly. The feedback will be given by a lecture directly after the session of class is end.English is chosen as the language used because it is needed in the modern era. Most of students believed that speaking is the most difficult skill in learning English.However, it can be handled by having good habit in speakings practices.The object of this study is some students on Faculty of Languages and Arts of Semarang State University. The object is needed to test the role of E-talk Castel?s model. Data is collected by doing observation and interview as a primary data, and by internet research and other sources which are relevant as a secondary data. Data is analyzed by using descriptive qualitative method. The result of the study is; students give good response for E-talk Castel?s model in increasing their speaking skill in English.